Pemberdayaan Ibu Dalam Menjaga Kesehatan Reproduksi Pada Situasi Bencana Di Desa Tetumpun Kabupaten Gayo Aceh - Tifani Hadi Tri Wahyuni (STIKES Columbia Asia Medan, 2026)
The landslide disaster that occurred in Tetumpun Village in June 2025 forced 45 families to take refuge. The evacuation conditions with limited access to clean water and sanitation posed high risks to reproductive organ hygiene problems among women. This community service activity aims to increase knowledge and skills of refugee mothers in maintaining reproductive organ hygiene. Implementation methods included reproductive health education, hygiene practice demonstrations, and distribution of hygiene kits. The activity was conducted for 1 day on July 15, 2025 and attended by 18 refugee mothers. Results showed an increase in participants' knowledge from an average of 52.78 (poor category) to 78.89 (good category) with an increase of 26.11 points (49.4%). All participants (100%) were able to practice proper reproductive organ cleaning methods after demonstration. Each participant received a hygiene kit containing sanitary pads, antiseptic soap, underwear, and other hygiene supplies. This activity successfully increased the capacity of refugee mothers in maintaining reproductive organ hygiene despite limited conditions.